Turkish-speaking christians in bulgaria - ALBERT HENRY; Bülent (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2025)
In the document titled "Turkish Speaking Christians in Bulgaria", the historical and ethnographic characteristics of the Gagauz are analyzed. The Gagauz are a Turkish-speaking Christian community with a long history dating back to pre-Ottoman times. The origins, traditions, language, and demographic structure of this community are discussed in detail in the document.